2020
DOI: 10.1101/2020.12.03.410290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in behavior drives multiscale responses to habitat conditions in timber rattlesnakes (Crotalus horridus)

Abstract: Variations in both the behavior of wildlife and the scale at which the environment most influences the space use of wild animals (i.e., scale of effect) are critical, but often overlooked in habitat selection modeling. Ecologists have proposed that biological responses happening over longer time frames are influenced by environmental variables at larger spatial scales, but this has rarely been empirically tested. Here, we hypothesized that long-term patterns of behavior (i.e. lasting multiple weeks to months) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Hoffman et al ( 2020 ) found that site selection associated with foraging, ecdysis, digestion, and gestation in this TRS population could be described by many of the landscape variables used in this study (Table 1 ) at behavior‐specific spatial scales (5–105 m). Foraging was negatively associated with temperature and a landscape moisture gradient (indicating drier soils and oak‐dominated areas), and these conditions did not describe site use for other behaviors (Hoffman et al, 2020 ). Importantly, TRS foraging was associated with cooler temperatures than sites associated with other behavioral states, suggesting that foraging behavior may be decoupled from snake thermoregulatory needs (Hoffman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Hoffman et al ( 2020 ) found that site selection associated with foraging, ecdysis, digestion, and gestation in this TRS population could be described by many of the landscape variables used in this study (Table 1 ) at behavior‐specific spatial scales (5–105 m). Foraging was negatively associated with temperature and a landscape moisture gradient (indicating drier soils and oak‐dominated areas), and these conditions did not describe site use for other behaviors (Hoffman et al, 2020 ). Importantly, TRS foraging was associated with cooler temperatures than sites associated with other behavioral states, suggesting that foraging behavior may be decoupled from snake thermoregulatory needs (Hoffman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 68%
“…Foraging was negatively associated with temperature and a landscape moisture gradient (indicating drier soils and oak‐dominated areas), and these conditions did not describe site use for other behaviors (Hoffman et al, 2020 ). Importantly, TRS foraging was associated with cooler temperatures than sites associated with other behavioral states, suggesting that foraging behavior may be decoupled from snake thermoregulatory needs (Hoffman et al, 2020 ). Our collective findings that TRS foraging is associated with greater prey availability but also suboptimal conditions for thermoregulation demonstrate that snakes preferentially seek out prey‐rich areas to forage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation